(3YeGdI GdChdGO GdadSWfjjf aj dHfGf (B: (3fehPL eNje HQL GdHQGLfIs - (3Ydj, Qaja CMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3GdeYgO GdYGdj ddOcJhQGg aj GdBOGH hGdYdhe GdEfSGfjI GdELJeGYjIs, 2009)
(3JgOa GdOQGSI Edi GdJYeb aj XGgQI YeGdI GdChdGO GdadSWjfjf aj dHfGf ef NdGd GdGWdGY Ydi TQhW Yedge hGdefTBJ GdJj jYedhf VefgG, hEdbGA GdVhA Ydi JCKjQGJ gPg GdYeGdI hYdi hVY GddGLF GdadSWjfj aj dHfGf ef fGMjI GdYed, hhVYg aj Shb GdYed, heG jfJL Yfg ef XQha GbJUGOjI hGLJeGYjI(B. (3HGdEVGaI Edi GdCSHGH GdOGaYI dJSQHge ef GdeOQSI hGfNQGWge aj Shb GdYed(B. (3EYJeOJ GdOQGSI GdYOjO ef GdefGgL, efgG GdefgL GdJMdjdj, efgL OQGSI GdMGdI, hGdefgL GdhKGFbj(B. (3Ted eLJeY GdOQGSI eNje HQL GdHQGLfI, aj GdVGMjI GdLfhHjI ddHfGf, hEJNPJ YjfI ef (B212 (3hdkOG adSWjfkqjG YGedkG, JJQGhM CYeGQge Hjf (B7 (3Edi (B17 (3SfI, heLehYI eDdaI ef (B50 (3QH CSQI dChdGO GdYjfI h (B31 (3UGMH Yed dHfGfj hadSWjfj, hGSJNOeJ JbfjI GdGSJeGQI, GdedGMXI, hGdebGHdI eY CQHGH CSQ GdChdGO hCQHGH GdYed, HGdEVGaI Edi GdebGHdI eY GddLfI GdTYHjI ddeNje hHYV GdLeYjGJ(B. (3HjfJ GdfJGFL MQeGf GdWad GdadSWjfj ef cKjQ ef Mbhb GdWad GdJj fUJ YdjgG GdGJaGbjGJ GdYGdejI, ceG hCXgQJ JYQV GdWad GdYGed dShA GdeYGedI, GdGSJZdGd, GdVQQ GdUMj, GdeNGWQ, hYOe GdJeJY HCj Mb WHjYj cHGbj GdCWaGd hNUhUG aj Xd GdSGYGJ GdWhjdI aj GdYed, aJHjf YOe JWHjb aYdj ddJTQjYGJ GdbGfhfjI GddHfGfjI Mhd Mbhb GdWad(B. (3XgQJ CSHGH GdJSQH GdeOQSj hJQc GdeOQSI eJYdbI CZdHjJgG HGdhVY GdEbJUGOj GdeJQOj ddCSQI hMGLJgG deUOQ ONd EVGaj, ceG hdYHJ GdNUGFU GdGLJeGYjI hGdJYdjejI ddCSQI HLGfH GdGbJUGOjI, OhQG aj QSe eSJbHd CHfGFge GdJYdjej hGdegfj(B. (3HGdEVGaI Edi GdQShH GdeJcQQ hhVY GdeOGQS hGaJbGQgG dYfUQ GdLPH, hNUhUkG eOGQS GdChfQhG, hShA GdeYGedI hGcJXGX GdUaha hYOe EdRGejI GdJYdje, OaY GdChdGO dJQc GdeOGQS hGdYed aj egf djSJ PGJ CgejI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Bourj EL Barajne camps; Bourj EL Barajne camps; Child Labor; Palestinians Education; Palestiniens; Travail des enfants; (3GdadSWjfjhfs; (3YeGdI GdGWaGd hCWaGd GdThGQYs; (3eNje HQL GdHQGLfIs